Why the Covenant Worked: On the Institutional Foundations of the American Civil Religion - Compton, John W. (Religions, 2019)
Scholars of American civil religion (ACR) have paid insufficient attention to the micro-level processes through which civil religious ideas have historically influenced beliefs and behavior. We know little about what makes such appeals meaningful to average Americans (assuming they are meaningful); nor do we know much about the mechanisms through which abstract religious themes and imagery come to be associated with specific policy aims, or what Robert Bellah called "national goals." This article argues that a renewed focus on the relationship between civil religion and organized religion can help fill this gap in the literature. More specifically, I draw attention to three mainline Protestant institutions that for much of the twentieth-century were instrumental both in cultivating respect for the national civic faith and in connecting its abstract ideals to concrete reform programs: namely, the clergy, the state and local church councils, and the policy-oriented departments of the National Council of Churches (NCC). Finally, I argue that a fresh look at the relationship between civil religion and "church religion" sheds new light on the (arguably) diminished role of civil religious appeals in the present. If, as Bellah claimed in his later writings, ACR appeals have lost much of their power to motivate support for shared national goals, it is at least in part because the formal religious networks through which they once were transmitted and interpreted have largely collapsed.